Faktor-Faktor yang Memengaruhi Penyerapan Tenaga Kerja pada UMKM Penerima Program Kredit Usaha Rakyat (KUR) di Pulau Jawa - Syafinah Az Zahra Yusufy; Dimas Nugroho Dwi Seputro (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in employment creation in Indonesia, yet their labor absorption capacity remains vulnerable to economic shocks, particularly during the COVID-19 pandemic. To support business continuity and job creation, the government implemented the People’s Business Credit (KUR) program to expand MSMEs’ access to formal financing. However, empirical evidence regarding the effectiveness of KUR in enhancing labor absorption remains limited. This study aims to analyze the influence of internal and external characteristics on labor absorption among MSMEs receiving KUR in Java. Using secondary data from the 2021 MSME KUR Recipient Survey, this study applies multiple linear regression with the Ordinary Least Squares (OLS) approach to a sample of 476 MSMEs. The independent variables include monthly business turnover, ownership of a business bank account, educational attainment of business owners, and business sector classification based on KBLI. The results indicate that monthly business turnover has a positive and significant effect on labor absorption, while business sector characteristics particularly transportation and warehousing also significantly influence employment levels. In contrast, ownership of a business bank account and the owner’s educational level do not show a significant effect. These findings suggest that business capacity and sectoral characteristics are key determinants of labor absorption and highlight the need for more targeted, sector-based MSME financing policies to support sustainable employment in the post-pandemic period.